Dietary Restriction in Drosophila: Delayed Aging or Experimental Artefact? - Piper, Matthew D. W (Public Library of Science, 2007)
Lifespan can be extended by reduction of dietary intake. This practice is referred to as dietary restriction (DR), and extension of lifespan by DR is evolutionarily conserved in taxonomically diverse organisms including yeast, invertebrates, and mammals. Although these two often-stated facts carry the implication that the mechanisms of DR are also evolutionarily conserved, extension of lifespan could be a case of evolutionary convergence, with different underlying mechanisms in different taxa. Furthermore, extension of lifespan by different methods of DR in the same organism may operate through different mechanisms. These topics remain unresolved because of the very fact that the mechanisms of DR are unknown. Given these uncertainties, it is essential that work on the mechanisms of DR is not clouded by imprecise descriptions of methods or by technical problems. Here we review the recent literature on DR in Drosophila to point out some methodological issues that can obscure mechanistic interpretations. We also indicate some experiments that could be performed to determine if DR in Drosophila operates through similar mechanisms to the process in rodents.